Bilateral Obturator Hernia Diagnosed by Computed Tomography: A Case Report with Review of the Literature - Sanjay M. Khaladkar; Anubhav Kamal; Sahil Garg; Vigyat Kamal (Radiology Research and Practice)
Obturator hernia is a rare form of abdominal hernia and a diagnostic challenge. It is commonly seen in elderly thin females. Its diagnosis is often delayed with resultant increased morbidity and mortality due to bowel ischemia/gangrene. It is mistakenly diagnosed as femoral or inguinal hernia on USG. Computed tomography is diagnostic and is a valuable tool for preoperative diagnosis. This report presents a case of 70-year-old thin female presenting with intestinal obstruction due to left sided obstructed obturator hernia. USG showed small bowel obstruction and an obstructed left sided femoral hernia. CT scan of abdomen and pelvis with inguinal and upper thigh region disclosed left sided obturator hernia. It also detected clinically occult right sided obturator hernia. Early diagnosis and surgical treatment contribute greatly in reducing the morbidity and mortality rate.